2021
DOI: 10.1016/j.cub.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis-induced activation of anion channel SLAH3 in the flooding-related stress response of Arabidopsis

Abstract: Highlights d Cytosolic acidosis triggers SLAH3-mediated anion efflux in planta d SLAH3 is directly activated by protonation of two specific histidine residues d Upon cytosolic acidification, SLAH3 dimers monomerize, leading to channel activation d SLAH3 plays a role in plant responses to hypoxia under flooding conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 86 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…Phosphorylation has been widely reported to modulate the function of ion channels or transporters in plants. For example, phosphorylation modulates the activity of SLAH/SLAC anion channels through stoichiometry change 27 , 28 . And phosphorylation by CIPK23 and CBL1 may activate HAK5 by releasing the autoinhibitory domain 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation has been widely reported to modulate the function of ion channels or transporters in plants. For example, phosphorylation modulates the activity of SLAH/SLAC anion channels through stoichiometry change 27 , 28 . And phosphorylation by CIPK23 and CBL1 may activate HAK5 by releasing the autoinhibitory domain 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The latter is exemplified by the regulation of anion channels in guard cells that convey adaptation to drought and osmotic stress. Here, the SLAC1 channel as well as related SLAH channels are subject to regulation by the combined function of several CDPKs and CBL-CIPK complexes (Geiger et al, 2010;Brandt et al, 2012Brandt et al, , 2015Scherzer et al, 2012;Maierhofer et al, 2014;Lehmann et al, 2021). Currently, it remains to be clarified if these multiple kinases provide alternative paths of ion channel activation or if they also convey additive levels of ion transport enhancement.…”
Section: Getting the Message: Components And Mechanisms Decoding Stre...mentioning
confidence: 99%
“…For the reason that ELF3 functions antagonistically with PHYTOCHROME-INTERACTING FACTOR4 (PIF4) in thermomorphogenesis (Raschke et al, 2015), we also found their conversed expression pattern in H. difformis. The proton sensor SLAC1 HOMOLOGUE 3 (SLAH3) (Lehmann et al, 2021), the mechanical stimuli sensor MSCS-LIKE 10 (MSL10) (Tran et al, 2021), and aquaporins Plasma membrane Intrinsic Proteins (PIPs) (Yaneff et al, 2015) are also significantly upregulated in terrestrial conditions. Morphological changes in leaf shape are the most obvious characteristics in heterophyllous plants.…”
Section: Morphological Physiological and Molecular Adaptation Of H Di...mentioning
confidence: 99%